(untitled) (Journal of actual problems of jurisprudence, 2018)
This article is sanctified to the questions of implementation of scientific research within the framework of institution of higher learning. Experience of implementation of scientific research forces of teachers, city councils, докторантов and students opens up. Drawn conclusion that in the process of educating in institution of higher learning maybe and it is necessary to expose the scientific capabilities of students. Also to this article experience of realization of sociological research of sense of justice and legal culture of young people is driven. Key words: right, legal culture, scientific research, sociological questioning, young people, students, master’s degrees.